Strategi Komunikasi Corporate Social Responsibility PT Dwi Mitra Daya Riau Dalam Pemberdayaan Masyarakat Bukit Badak - Maimunah Haitami; Arifin Saleh (Universitas Muhammadiyah Sumatera Utara, 2023)
This research is motivated by the implementation of community empowerment through the Corporate Social Responsibility (CSR) program which is constrained due to communication problems between the activity manager and the community targeted by the activity program. This communication problem varies, from the content or communication messages related to the program, the communicator, to the communication media. Departing from this, it is deemed necessary to have a communication strategy for CSR programs in an effort to empower the community. The purpose of this research is to find out the CSR communication strategy of PT Dwi Mitra Daya Riau in empowering the Bukit Badak community. The theories used in this research are communication strategy theory, CSR communication, and community empowerment. This type of research is descriptive with a qualitative approach using interview, documentation, and observation methods. Data analysis is carried out using qualitative descriptive analysis method, which describes the data obtained through research instruments with 5 sources, including 1 public relations person of PT Dwi Mitra Daya Riau, and 1 employee of PT Dwi Mitra Daya Riau and 3 people from the Bukit Badak community. The results of this study indicate that PT DwiMitra Daya Riau's CSR communication strategy in empowering the Bukit Badak community with the existence of Bilikom (Community Development and Communication) can help and facilitate the community to communicate directly with PT Dwi Mitra Daya Riau so that PT Dwi Mitra Daya Riau can more easily communicate directly with the Bukit Badak community so that the CSR programs that will be implemented by PT Dwi Mitra Daya Riau can be understood by the Bukit Badak community. Some of PT DwiMitra Daya Riau's Corporate programs in community empowerment such as programs in education, health, and agriculture with the CSR programs provided by PT Dwi Mitra Daya Riau hopefully can help the people in Bukit Badak